Competence and organizational commitment to performance through job satisfaction in bps west Sumatera region - Afuan, M.; Ali, Hapzi; Zefriyenni, Zefriyenni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The purpose of this study is to examine how job satisfaction among employees of the West Sumatra Regional Central Statistics Agency affects competence and organisational commitment on performance. Using the Slovin technique, 269 samples were found to meet the study's criteria. In research, questionnaires chosen by proportional random sampling are distributed, and SmartPLS3 is used to test the data. The study's findings demonstrate that while organisational commitment has a significant impact on job satisfaction, competence has no significant effect on performance, job satisfaction has a significant impact on performance, and job satisfaction is able to job satisfaction has the ability to mediate organisational commitment to performance, and competence can mediate performance.